Organosulfide-plasticized solid-electrolyte interphase layer enables stable lithium metal anodes for long-cycle lithium-sulfur batteries. Issue 1 (December 2017) - Li, Guoxing; Gao, Yue; He, Xin; Huang, Qingquan; Chen, Shuru; Kim, Seong; Wang, Donghai
Abstract Lithium metal is a promising anode candidate for the next-generation rechargeable battery due to its highest specific capacity (3860 mA h g−1 ) and lowest potential, but low Coulombic efficiency and formation of lithium dendrites hinder its practical application. Here, we report a self-formed flexible hybrid solid- electrolyte interphase layer through co-deposition of organosulfides/organopolysulfides and inorganic lithium salts using sulfur- containing polymers as an additive in the electrolyte. The organosulfides/organopolysulfides serve as "plasticizer" in the solid- electrolyte interphase layer to improve its mechanical flexibility and toughness. The as-formed robust solid- electrolyte interphase layers enable dendrite-free lithium deposition and significantly improve Coulombic efficiency (99% over 400 cycles at a current density of 2 mA cm−2 ). A lithium- sulfur battery based on this strategy exhibits long cycling life (1000 cycles) and good capacity retention. This study reveals an avenue to effectively fabricate stable solid- electrolyte interphase layer for solving the issues associated with lithium metal anodes. The practical application of lithium metal anodes suffers from the poor Coulombic efficiency and growth of lithium dendrites. Here, the authors report an approach to enable the self-formation of stable and flexible solid-electrolyte interphase layers which serve to address both issues.